KAJIAN SERBUK BIJI PINANG (ARECA CATECHU, L.) SEBAGAI BAHAN BAKU KOMPOS - Fikri Arsil (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
This research is purposed to measure the raw material of compost, the content of hara compost, exemine the best composition areca palm nut grain powder as compost raw material and comparing organe fertilizer specification that observed by Indonesian Nasional Standar of Compost (SNI). This studying is implemented in several term, the process of micsuring raw material and fermentation. The process of micsuring raw material is given three treatments in volume weight of compost raw material. The raw material used is areca palm nut powder, thitonia and chicken dust. Observed parameter during manuring process is temperature, humidity, aeracy and time inversion in three repeatation each observation. When the compost has been being ripe the examination hara substance done. (2 : 1 : 1) compost of areca palm nut powder compared with composition of the others with K.A 22,42 %, N 3,36 %, P 0,85 %, K 2,83 %, C 37,97 %, C/N 11,29 and pH 6,69. Areca palm seed nut powder etrety has been finished in Compost Quality Indonesia National Standar (SNI).